2012
DOI: 10.1093/jnci/djr516
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Classical Hodgkin Lymphoma and Epstein–Barr Virus Status–Defined Subgroups

Abstract: Overall, these results provide strong evidence that EBV status is an etiologically important classification of cHL and also suggest that some components of the pathological process are common to both EBV-positive and EBV-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
134
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 52 publications
11
134
1
2
Order By: Relevance
“…However, the impact of HLA class I on EBV latency antigen‐specific CD8 + T cell immunity has not been determined systematically. Interestingly, large epidemiological and genomewide association studies have consistently reported differential HLA class I susceptibility to EBV + cHL (Supporting information, Table S1) 14, 15, 16, 17. In western European populations, HLA‐A*01 and HLA‐B*37 are associated with increased susceptibility to EBV + cHL, while HLA‐A*02 is associated with protection 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of HLA class I on EBV latency antigen‐specific CD8 + T cell immunity has not been determined systematically. Interestingly, large epidemiological and genomewide association studies have consistently reported differential HLA class I susceptibility to EBV + cHL (Supporting information, Table S1) 14, 15, 16, 17. In western European populations, HLA‐A*01 and HLA‐B*37 are associated with increased susceptibility to EBV + cHL, while HLA‐A*02 is associated with protection 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Although T-cell and NK cell can also be infected by EBV, it mainly attacks B lymphocytes, thus the most common forms of EBVassociated lympho-proliferative disorders are B-cell lymphomas such as HL, Burkitt Lymphoma and diffuse large B-cell lymphoma (DLBCL) [24][25][26][27]. In nearly half of HL patients, the genome of EBV can be found [28][29][30]. Notably, EBV is more commonly associated with mixedcellularity HL and lymphocyte-depleted HL [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In nearly half of HL patients, the genome of EBV can be found [28][29][30]. Notably, EBV is more commonly associated with mixedcellularity HL and lymphocyte-depleted HL [28][29][30]. Therapeutic regimen for both EBV positive and negative cases of HL is currently identical, with long term remissions in most patients, but relapsed EBV positive HL patients have a poor prognosis [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…We re-examined five previously discovered single nucleotide polymorphisms (SNPs) of known associations to leukemia (rs7089424, rs10821936, rs10994982, rs4132601, and rs2239633), along with three HLA region susceptibility markers for lymphomas, since lymphoma and ALL both stem from lymphoid cells. These included rs2395185, a marker of HLA DRB4 lineage [23] which has previously shown associations with major leukemias including childhood ALL [24,25] and other diseases including Hodgkin lymphoma [26], lung cancer [27], rheumatoid arthritis [28], asthma [29], and ulcerative colitis [30][31][32]; rs10484561, which has been shown to be a strong risk marker in follicular lymphoma (FL) [33]; and rs2647012, which is a protective marker for FL [34]. These SNPs were examined in a multiethnic sample (non-Hispanic Whites, Hispanic Whites, and Blacks) from Houston, Texas to assess their association with ALL.…”
Section: Introductionmentioning
confidence: 99%